SOCIO-ECONOMIC LIFE DEVELOPMENT OF KEMPLANG BUSINESS COMMUNITY IN PEDAMARAN VILLAGE 2011-2023: Social Economy - Edenia, Balqis; Yusuf, Syafruddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the role of kemplang production as a key economic activity among the community of Pedamaran Village, Ogan Komering Ilir, South Sumatra, and its influence on local socio-economic conditions. As a traditional food product, kemplang functions not only as a consumable commodity but also as an important source of income for many households. The research employs a descriptive qualitative approach through literature review, direct observation, and in-depth interviews with local kemplang producers. Secondary data from village documentation and relevant literature further support the analysis. The findings indicate that kemplang enterprises significantly contribute to household income and strengthen women’s economic independence through their active participation in production activities. In addition, this enterprise fosters social networks within home-based industries, supporting the sustainability of the local economy. The long-standing tradition of kemplang production, passed down through generations, also helps preserve cultural values and reinforce the community’s cultural identity. Despite its considerable potential, producers continue to face challenges related to marketing, product innovation, and access to capital. Therefore, support from the government and private sector is essential to enhance business capacity and develop this local economic potential in a sustainable manner.